Nanoemulsion as a promising drug delivery strategy for effective eradication of Helicobacter pylori: current insights - Moumita Saha; Ashutosh Gupta; Shivani Kunkalienkar; Namdev Dhas; Shiran Shetty; Abhishek Gupta; Srinivas Mutalik; Nandakumar Krishnadas; Raghu Chandrashekar; Nagalakshmi Narasimhaswamy; Sudheer Moorkoth (Drug Delivery and Translational Research, 2026)
Helicobacter pylori ( H. pylori ) have infected about 50% of the world’s population and is a leading cause of gastrointestinal diseases, including gastritis, peptic ulcer, and stomach cancer. Current treatment regimens often fail to completely eradicate the bacteria due to the failure of antibiotics to penetrate into stomach’s inner mucosa, where the bacteria reside. Additional factors such as the ability of the organism to neutralize the stomach’s acidic environment and biofilm formation further contribute to treatment failure leading to antibiotic resistance. These challenges underscore the urgent need for new treatment options and strategies to combat H. pylori effectively. The current review delivers an overview of the pathophysiology of H. pylori , the limitations of the current regimens, and the potential of nanoemulsion as a smart carrier addressing the limitations associated with H. pylori treatment. The nanoemulsion offers specific advantages like mucoadhesion potential, targeted delivery, controlled release, and co-delivery options that ultimately results in an enhancement of bioavailability of the antibiotics to H. pylori , which resides in the inner walls of the stomach mucosa. Further, the ability of nanoemulsions to encapsulate the drug molecules helps in protecting the antibiotics from the stomach acidity facilitating drug stability. In conclusion, the review highlights the importance of tapping this unexplored potential of nanoemulsion as a promising drug delivery option for the treatment of H. pylori infection. Graphical abstract

Emerging trends in chitosan based colloidal drug delivery systems: A translational journey from research to practice - Mahadev Manohar; Amitha Shetty; Cynthia Lizzie Lobo; Praneetha Jain; Srinivas Hebbar; Namdev Dhas; Kishori P. Sutar; Johan Sukeewandhi; Haribalan Perumalsamy; Sri Renukadevi Balusamy; Yahya F. Jamous; Akhilesh Dubey; et al. (Carbohydrate Polymers, 2025)

Sulfobutylether-β-cyclodextrin: A functional biopolymer for drug delivery applications - Chandrakantsing V. Pardeshi; Rucha V. Kothawade; Ashwini R. Markad; Sagar R. Pardeshi; Abhijeet D. Kulkarni; Prashant J. Chaudhari; Marcela R. Longhi; Namdev Dhas; Jitendra B. Naik; Sanjay J. Surana; Mónica C. García (Carbohydrate Polymers, 2023)

Advances in 4D printing: from stimulation to simulation - Prashant Pingale; Shilpa Dawre; Vividha Dhapte-Pawar; Namdev Dhas; Amarjitsing Rajput (Drug Delivery and Translational Research, 2023)

Emerging Nanomedicines for the Treatment of Atopic Dermatitis - Khushali Parekh; Tejal A Mehta; Namdev Dhas; Pavan Kumar; Amirali Popat (AAPS PharmSciTech, 2021)